PROSPECTS OF RAINBOW TROUT - ONCORHYNCHUS MYKISS, WALBAUM CULTURE IN MID ALTITUDES OF CENTRAL HIMASLAYAS, INDIA - VASS, K. K.; RAINA, H. S.; HALDAR, R. S. (Journal of the Inland Fisheries Society of India, 2022)
In temperate regions, the relatively short growing season requires technologies, which can result in high biomass during available growing period. Therefore, to achieve higher growth rates, seasonality factor has to be blended with better aquaculture practices with a focus on diets and environment. This study aims at evaluating the influence of higher water volume, modified culture system and temperature on growth and survival of a fast growing strain of rainbow trout-Oncorhynchus mykiss (Norwegian strain). The fishes were reared exclusively on groundwater at a temperature range of 10.0-21.0 0 C. Experimental trials were carried out in FRP tanks of 2.0 m2 , the stocks were fed with two different protein and energy content diets. The comparative growth rates over a period of one year at different temperature regimes with two diets have been analyzed. A slightly better growth was found for fish fed on high-energy contents and on low fat feed at higher temperature. The results suggest that the species is well suited for aquafarming in mid-altitudes of Central Himalayas and adoption on commercial scale by entrepreneurs is promising.Keywords : Rainbow trout, status, cultural possibilities, mid altitudes, Himalayas.